Economic and Environmental Assessment of the Wine Chain in Southeastern Spain - José García García; Begoña García Castellanos; Benjamín García García (Agronomy, 2023)
The sustainability of the wine chain in the southeast of Spain is evaluated through life cycle costing (LCC) and life cycle assessment (LCA) methodologies. A winery model is established based on the information provided by representative companies in the area. The LCC and LCA are applied to the production of the wine bottle, and a sensitivity analysis is applied to evaluate the effect of the different types of vineyard, as well as the weight of the glass bottle. In the cellar phase, the processes are highly technical and are very efficient in relation to the consumption of energy, water, and other inputs. However, the weight of the glass bottle should be minimized as it has a great impact on both environmental and production costs. The socioeconomic importance of the wine chain is relevant, both in quantitative terms and for what it means as a brand transmission mechanism for the agri-food sector. It should also be taken into account that the environmental cost of the processes is low, and that the activity contributes to the conservation of the soil and landscape in a semi-arid area.